Predictive factors and clinicopathological characteristics of outcome in poorly differentiated thyroid carcinoma: a single-institution study - Wan, Zheng; Wang, Bing; Yao, Jing; Li, Qing; Miao, Xin; Jian, Yanbing; Huang, Sisi; Lai, Shengwei; Li, Chen; Tian, Wen (Frontiers in Oncology, 2023)
Objective To elucidate the clinicopathological characteristics and prognostic factors of poorly differentiated thyroid carcinoma. Method A total of 24912 thyroid carcinoma patients admitted to the First Medical Center of Chinese People’s Liberation Army General Hospital from 2005 to 2020 were retrospectively reviewed. A total of 94 patients (39 males and 55 females, a male-female ratio of 1:1.4) fulfilled the selection criteria. Of these, 73 patients had undergone surgery. The clinical and pathological data were collected from each enrolled patient. Univariate and multivariate Cox regression analyses were performed to determine independent prognostic factors. All analyses were performed with the SPSS version 26.0 and R version 1.2.5033 in the R Studio environment. Results The specimens included 20 cases of poorly differentiated thyroid carcinoma complicated with papillary thyroid carcinoma, 17 cases complicated with follicular thyroid carcinoma, 34 cases complicated with other pathological types and 23 with a separate entity. The patient demonstrated a large age span, median age was 57 years (range 8–85 years, average 55.20±15.74 years). The survival time of the 94 cases was calculated, and the mean Overall survival time was 33 (range, 1-170) months, and the mean Recurrence-free survival time was 14 (range, 1-90) months. Recurrence-free mortality is related to the age at diagnosis , extrathyroidal extension and Associated thyroid cancer (p＜0.05). In contrast, overall mortality is related to the age at diagnosis, sex, extrathyroidal extension, T stage (AJCC 8th), surgery and radiation (p＜0.05). Conclusions Middle-aged and elderly patients are still at high risk for poorly differentiated thyroid carcinoma. The pathologic results of poorly differentiated thyroid carcinoma are varied, and reasonable treatment has an important impact on the prognosis of poorly differentiated thyroid carcinoma.